Expression Profiles and Functional Characterization of Chemosensory Protein 15 (HhalCSP15) in the Brown Marmorated Stink Bug Halyomorpha halys - Wang, Zehua; Yang, Fan; Sun, Ang; Shan, Shuang; Zhang, Yongjun; Wang, Shanning (Frontiers in Physiology, 2021)
Chemosensory proteins (CSPs) have been identified in the sensory tissues of various insect species and are believed to be involved in chemical communication in insects. However, the physiological roles of CSPs in Halyomorpha halys, a highly invasive insect species, are rarely reported. Here, we focused on one of the antennal CSPs (HhalCSP15) and determined whether it was involved in olfactory perception. Reverse transcription PCR (RT-PCR) and quantitative real-time PCR (qRT-PCR) analysis showed that HhalCSP15 was enriched in nymph and male and female adult antennae, indicating that it is involved in the perception of semiochemicals, and thus, mediates common olfactory behaviors in H. halys. Fluorescence competitive binding assays revealed that three of 43 natural compounds showed binding abilities with HhalCSP15, including β-ionone (Ki = 11.9 μM), cis-3-Hexen-1-yl benzoate (Ki = 10.5 μM), and Methyl (2E,4E,6Z)-decatrienoate (EEZ-MDT) (Ki = 9.6 μM). Docking analysis supported the experimental affinity for the three ligands. Additionally, the electrophysiological activities of the three ligands were further confirmed using electroantennography. EEZ-MDT is particularly interesting, as it serves as a kairomone when H. halys forages for host plants. We therefore conclude that HhalCSP15 may be involved in host-finding behavior. Our data provide a basis for further investigation of the physiological roles of CSPs in H. halys, and extend the olfactory function of CSPs in stink bugs.